Flow-Through Portable Antivirus UV-C Optical Enclosures to be Used with Protective Masks - Ozgur Selimoglu (International Journal of Optics)
UV-C light is an important disinfection tool against airborne viruses, while also being harmful if the light reaches the human skin. Body-attached reflective flow-through optical enclosures can be used for isolating the UV-C light from the user as well as elevating the irradiance level. In this study, we explain why air-sterilizing light enclosures are more effective than the expectations by introducing a dose multiplication factor of 4. As a result of omnidirectional illumination, air sterilization becomes more effective than surface disinfection if similar irradiance levels are measured from the enclosure wall. The methodology is explained by the design of a portable enclosure device primarily targeting the COVID-19 virus, and disinfection effectiveness better than 99.5% is demonstrated by biological tests.